Studying comics and graphic novels - Kukkonen, Karin (WILEY, 2013)
This introduction to studying comics and graphic novels is a structured guide to a popular topic. It deploys new cognitive methods of textual analysis and features activities and exercises throughout. * Deploys novel cognitive approaches to analyze the importance of psychological and physical aspects of reader experience * Carefully structured to build a sequenced, rounded introduction to the subject * Includes study activities, writing exercises, and essay topics throughout * Dedicated chapters cover popular sub-genres such as autobiography and literary adaptation